George Eliot, the queen of fiction - Kimball, Stella Victoria (My University, 1894)
Introduction: This is an age of novelists. Each kind of literature has had its period of greatest prominence. All through history poetry has been the first to reappear after a period in which the literature has been suppressed. The drama, the essay, and religious writing each had their day, and poetry was hardly more prominent then than now. But, in the words of a writer – “The novelist can stretch a wider canvas than the poet and on his palette he has a greater variety of pigments where with to produce his picture in its lights and glooms.” The year 1740 gave birth to the first novel, Pamela, written by Samuel Richardson. But not even in their dreams did a vision of the novel of today even cross the minds of the people of the early part of the eighteenth century. Henry Fielding and Tobias Smollett were writers of the same period, and these three early writers we class as the first great group of novelists. With the Vicar of Wakefield in 1766, by Goldsmith, we find the novel in a different use, for the Vicar of Wakefield was to the novel, what Wordsworth’s poems were to the poetry of their day—descriptions of country life and scenes.
Citation: Kimball, Stella Victoria. George Eliot, the queen of fiction. Senior thesis, Kansas State Agricultural College, 1894.
Morse Department of Special Collections
Keywords: Fiction; :Literature; English; George Eliot; Writer; Novel; Pre-novel; Theses; Manuscripts (documents)